2018
DOI: 10.1111/bcp.13556
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of persistent prescription opioid analgesic use among people without cancer in Australia

Abstract: Patient-specific characteristics (older age, prior history of mental health comorbidities and use of non-opioid analgesics) and prescriber choice of initial opioid (transdermal formulation and higher total OMEs) were found to strongly predict persistent use. This information may help prescribers target monitoring and early intervention efforts in order to prevent harms associated with the long-term use of opioids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 51 publications
(93 reference statements)
8
63
2
Order By: Relevance
“…Also, by using medications as a surrogate to identify persons with comorbidities, people on non‐pharmacological approaches for managing their condition may have been missed. Regardless, the Rx‐Risk‐V tool that was used in identifying comorbidities has been validated and widely used by Australian and international researchers to ascertain the presence of chronic morbidities . We were also unable to stratify our results according to statin indication and future studies should examine predictors specifically for people being prescribed statins for primary and secondary prevention.…”
Section: Discussionmentioning
confidence: 98%
“…Also, by using medications as a surrogate to identify persons with comorbidities, people on non‐pharmacological approaches for managing their condition may have been missed. Regardless, the Rx‐Risk‐V tool that was used in identifying comorbidities has been validated and widely used by Australian and international researchers to ascertain the presence of chronic morbidities . We were also unable to stratify our results according to statin indication and future studies should examine predictors specifically for people being prescribed statins for primary and secondary prevention.…”
Section: Discussionmentioning
confidence: 98%
“…Comorbidities were determined using the validated RxRisk‐V tool, which uses records of dispensed medications to identify probable medical conditions . A full list of medications and their respective medical conditions is reported elsewhere . A look‐back period of 12 months from the date of opioid initiation was used to establish probable comorbidities.…”
Section: Methodsmentioning
confidence: 99%
“…Previous Australian research has indicated that the RxRisk‐V tool identifies fewer people with cancer compared to the Charlson's Comorbidity Index (43.2 versus 67.2%), which is widely used and considered a ‘gold standard’ approach to assess disease burden . For this reason we used a more comprehensive medication‐based indicator of cancer treatment that included other anti‐neoplastic therapies such as hormonal cancer therapies . Cancer treatment history was used as a predictor because cancer‐related pain could influence the rate of opioid transitions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known about the development of chronic opioid prescription in older adults. One recent study of older Australians without malignancy found that people aged 75 years or more who were prescribed opioids were 2.5 times more likely to persist with long‐term opioid use than those aged 18‐44 years . A prior history of depression, use of non‐opioid analgesics and prescriber choice of initial opioids (transdermal formulation and high oral morphine equivalent) were all associated with long‐term opioid use in older Australians .…”
mentioning
confidence: 99%